Borrowing, loss of income and related sociodemographic factors in post-traumatic stress disorder in COVID-19 patients: A cross-sectional study from a government hospital in Mumbai, India - Amit Bhondve; Shruti Vijay Tilak; Nived G. Sudarson; Shermeen Rajesh More; Prashant Harish Saraf; Shreyansh Dinesh Singh; Eeshwari Vinay Lele; Ritu Mohit Shah; Kavya Amitabh Shah; Diya Padam Mehra (Indian Journal of Community and Family Medicine)
Introduction: Socioeconomic and related demographic characteristics may contribute to psychological distress following hospitalization with COVID-19. Financial strain experienced during the hospital stay may be associated with a heightened risk for posttraumatic stress disorder (PTSD). Material and Methods: The present study aimed to assess the prevalence and socioeconomic correlates of PTSD among patients previously hospitalized with COVID-19 in a government hospital in Mumbai, India, through a cross-sectional, questionnaire-based study design. Patients were contacted through telephonic interviews 3 months following discharge. The questionnaire included demographic and socioeconomic details in relation with COVID-19 hospitalization and the PTSD Checklist for DSM-5 (PCL-5). Results: Only (6.7%) patients received a provisional diagnosis of PTSD, while 12/89 (13.5%) were classified as having subthreshold PTSD. 10/89 (11.2%) scored ≥31 on the PCL 5 and had probable PTSD. 10/89 (11.2%) scored ≥31 on the PCL-5. On bivariate analyses, being unmarried or divorced or separated (P = 0. 037), having children who were minors (P = 0. 002), traveling from outside the state for hospitalization (P < 0.001), borrowing (P = 0.002), or loss of income (P = 0.028) due to hospitalization were significantly associated with subthreshold PTSD. On multivariable analysis, borrowing (adjusted odds ratio [AOR] 9.45, 95% CI 1.08–82.72) and traveling from outside the state (AOR 35.75, 95% CI 1.46–875.45, P = 0.028) retained significance for subthreshold PTSD. Conclusion: Socioeconomic factors may contribute to PTSD burden in previously hospitalized COVID-19 patients. This points to a need for mental health screening and economic relief measures in financially vulnerable patients.